Naná Vasconcelos' Black Creative Praxis (Orfeu, 2025)
Naná Vasconcelos is one of the avatars of Brazilian experimental music, having elevated percussion, and specifically the berimbau, to international solo prominence. Ignored by the environment and narratives regarding both what has become established as Brazilian instrumental music and the discursive environment of experimentalism in these territories, this article presents the trajectory and production of this artist through his traits of innovation, experimentation, and invention, problematizing the limitations of biased perceptions that, unable to read the innovations in Afro-diasporic epistemologies, silence and reduce these exploratory Black productions to the sphere of the folkloric and the exotic. We will analyze Naná's work through the analytical framework of Black Creative Praxis, which investigates experimental Black productions in their conditions of creation, in order to detect how artists with creatively disruptive productions consolidated their careers in a field as conservative as the music market. By identifying the organizational methods employed in the international reach of such an innovative and global body of work as Naná Vasconcelos's, this study aims to deepen our understanding of aesthetics and ethics in musical experimentalism, since political and social struggles have historically informed artistic practices in Black imaginations.
Keywords: experimentalism; avant-garde; music; creativity; exoticism